Pengembangan Media Pembelajaran Interaktif Berbasis Canva pada Materi Shalat Jamak dan Qashar Kelas VII MTsN 7 Agam - Habib Siddieq; Zulfani Sesmiarni (YASIN, 2026)
Although interactive digital learning media have received considerable attention in Islamic religious education, studies that specifically discuss the development of Canva-based interactive media on the topic of combined and shortened prayers in Madrasah Tsanawiyah remain limited. This study aims to develop and test the validity, practicality, and effectiveness of Canva-based interactive learning media in fiqh learning on the topic of combined and shortened prayers in seventh grade. This study used a research and development approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected from three expert validators, namely material, media, and language experts, as well as 32 students from the trial class VII.6 and 30 students from the research class VII.7 at MTsN 7 Agam. The research instruments included validation sheets, teacher and student response questionnaires, and pre-test and post-test questions, and the data were then analyzed descriptively using a Likert percentage scale. The results showed that the developed learning media had a very high level of validity in the aspects of material at 100%, media at 96%, and language at 100%. The practicality of the media was also in the very high category, as indicated by teacher responses of 100% in both classes and student responses of 96.72% and 98.55%. The effectiveness of the media was very high, with an increase in learning outcomes from 71.03% to 94.13% in the trial class and from 70.76% to 95.38% in the research class, as well as an overall effectiveness of 94.75%. These findings contribute to the development of Canva-based interactive learning media in fiqh learning and expand the application of the ADDIE model in the context of Islamic religious education. The conclusion of this study affirms that Canva-based interactive learning media are feasible, practical, and effective for use as an alternative fiqh learning medium that is accessible, engaging, and supportive of improving students’ learning outcomes.